Kepemimpinan Kiai dalam Memelihara Budaya Organisasi di Pondok Modern Gontor , Lirboyo Kediri, dan Pesantren T ebuireng Jombang - Mardiyah Mardiyah (TSAQAFAH, 2012)
Islamic Boarding has been known as a model of education institution which has a competitiveness either in the tradition of knowledge seen as one of the great tradition or in its moral transition and transmission internalization. In the other sides, pesantren is also an education that can play the empowerment role and civil society transformation effectively . Kiai as a  leader of  pesantren has also an  important  role  in developing pesantren tradition  to  form  institution character  that  can differentiate with  the other. Because institution character as organization identity can be meant as a substantial point of the institution competitiveness  in  forming  process  that  indicates  two points, namely:  the growth of scientific tradition and the clean system of pesantren education management. This  research  is to answer research questions by analyzing: 1.  the structure of culture organization developed by Kiai as  leader, 2. Kiai  leadership  in keeping culture organization, 3. the similarity and difference of  the three pesantren. Based on qualitative paradigm, this research uses qualitative paradigm in terms of  phenomenological approarch which is meaningful  in comprehending  event  in  relation  to people  in  certain  situation. The process of this research uses multi-case studies because it is as inquiry that investigates empirically the phenomena in the real life context. The naturalistic paradigm chooses a sample purposively or by theoretically , three pesantren, namely: Pondok Modern Gontor, Lirboyo Kediri and Pesantren Tebuireng Jombang. The reason of  choosing the setting is based on some consideration on their specialty, uniqueness, interest, and suitable with the research topic.